Conscious materialistic realization: Bediuzzaman Said Nursi’s concept - Mohammad Tolba Said, Mohammad; Umachandran, Krishnan; Abd Rashid, Adnan (Universitas Lampung, 2018)
The reality of consciousness and cognition has consequences that are comparably pervasive; while subjectivism, realism and naturalism depended on science for valued truthful response. A strong connection to and advancement of the underlying idea of knowledge accumulation is to the contest alongside socialism and instinctive sympathy or fellow feeling between people with something in common. Bediuzzaman Said Nursi’s view of modern science and innovative references for development are covered here. Modern civilization is the product of the thought of integrating the natural sciences with the religious sciences to strengthen the truths on beliefs. His strong preaching’s under laid peace and harmony do not use any force and avoid any disruption. Public order and security must be maintained, and any damage caused by unbelief forces could be repaired by the healing truth of the Quran.